Determination of technical measurement uncertainty and method verification for coliform detection using the Multiple Tube Fermentation method in drinking water in sealed containers, ice, and raw water samples - wongsrikeaw, Denchai; Jamklang, Mantana; wangboon, Chompunoot; Kiatprasert, ‪Pongpat; Penkhrue, Watsana (Bulletin of Applied Sciences, 2026)
Coliform bacteria are a group of microorganisms commonly used as bacteriological indicators for assessing the microbiological quality and hygiene of water and food products. However, most laboratories in Thailand still lack verification data for microbiological analytical methods in accordance with ISO 16140-3:2021, which is essential for enhancing laboratory competence and supporting ISO/IEC 17025 accreditation. The determination of the Standard Deviation for Intralaboratory Reproducibility (SIR) and the method verification serves as definitive evidence that a laboratory can competently perform reference methods to ensure accurate and reliable results for clients. This study aimed to evaluate laboratory capability in quantifying coliform bacteria across various water samples, including bottled drinking water, ice, raw water, food-contact surface water, and deionized (DI) water. The evaluation determined the SIR and the Estimated bias (eBias) using the Multiple Tube Fermentation (MTF) method based on ISO 16140-3:2021 protocol for the verification of reference methods in a single laboratory. Three inoculation levels were evaluated: low (1 cfu/mL), medium (10 cfu/mL), and high (20 cfu/mL). The results revealed an overall SIR of 0.14. The eBias values for Group (A) samples were 0.00, 0.30, and 0.05 Log10 MPN/100 mL; for Group (B) samples were 0.18, 0.01, and 0.02 Log10 MPN/100 mL; and for Group (C) samples were 0.12, 0.06, and 0.05 Log10 MPN/100 mL, respectively. The method verification demonstrated that both SIR and the eBias values across all water types complied with the acceptability limit of ≤0.5 Log10 MPN/100 mL specified by ISO 16140-3:2021. This confirms that the laboratory can successfully implement the MTF method according to APHA, AWWA, and WEF standards with high accuracy and reliability. Consequently, these findings support the laboratory’s application for ISO/IEC 17025:2017 accreditation and demonstrate that this verified MTF technique is highly suitable for drinking water quality surveillance systems to protect public health.